A needs analysis for developing Canva-based interactive website media using the Contextual Teaching and Learning (CTL) approach in teaching English procedure text - Didik Rahmat Amin; Machdalena Vianty; Syarifuddin Syarifuddin (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2025)
This study investigates the learning needs of vocational students as the foundation for developing Canva-based interactive website media within the Contextual Teaching and Learning (CTL) framework. Using a descriptive mixed-method design implemented concurrently, the study involved 195 eleventh-grade students and three English teachers from SMKN 1 Talang Ubi. Data were collected through student questionnaires and teacher interviews to identify learning preferences, challenges in understanding procedure text, and expectations for digital learning tools. Quantitative findings reveal that visual (34%) and kinesthetic (22%) learning styles are the most dominant, and 90% of students report the need for media aligned with their learning styles. Additionally, over 60% of students experience frequent difficulties in learning, while classroom instruction remains largely dependent on textbooks (61%) with minimal use of interactive websites (14%). Qualitative interview results show that teachers rarely integrate digital or contextual media, and students often struggle with technical vocabulary, limited engagement, and insufficient real-life connections. These findings emphasize the need for interactive website media that incorporate visual clarity, contextual examples relevant to vocational fields, and opportunities for hands-on learning. The study concludes that a Canva-based interactive website grounded in CTL principles has strong potential to enhance students’ motivation, participation, and comprehension of procedure text. Future research is recommended to evaluate the effectiveness of the developed media through classroom implementation or experimental studies.